Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1159/000047118
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Mediators in Umbilical Plasma from Neonates Who Develop Early-Onset Sepsis

Abstract: Objectives: To study whether early-onset neonatal sepsis is associated with a prenatal immune response with elevated umbilical plasma levels of inflammatory mediators, and to study whether mediator levels may be helpful in identifying infected neonates. Setting: Nested case-control study. Methods: Cord blood was sampled from 7,073 consecutively delivered neonates. After review of the medical records, neonates suspected to suffer from infection were classified as infected (n = 52) or noninfected but sick contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 18 publications
6
61
0
5
Order By: Relevance
“…Furthermore, published values are generally Ͻ100 ng/L during sepsis in studies of both adults (30,(55)(56)(57)(58) and neonates (59 -63 ), which is well below peak concentrations found during experimental endotoxemia (54 ). Difficulties in using TNF␣ for sepsis diagnosis arise from the central role this cytokine plays in the inflammatory response, its short-term concentration in response to bacterial challenge, its short half-life of 17 min (64 ), and from excessive concentrations of soluble receptors p55 (sTNF-RI) and p75 (sTNF-RII) during sepsis (55,58,60 ).…”
Section: Biomarker Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, published values are generally Ͻ100 ng/L during sepsis in studies of both adults (30,(55)(56)(57)(58) and neonates (59 -63 ), which is well below peak concentrations found during experimental endotoxemia (54 ). Difficulties in using TNF␣ for sepsis diagnosis arise from the central role this cytokine plays in the inflammatory response, its short-term concentration in response to bacterial challenge, its short half-life of 17 min (64 ), and from excessive concentrations of soluble receptors p55 (sTNF-RI) and p75 (sTNF-RII) during sepsis (55,58,60 ).…”
Section: Biomarker Detectionmentioning
confidence: 99%
“…Studies involving neonates revealed similar diagnostic ambiguity, although ROC analyses demonstrated substantially higher mean specificity. The lower cutoff range stipulated in neonatal studies is indicative of the lower production of CRP in septic and healthy neonates, as is clearly reflected in values of 1-77 mg/L for septic and 0.1-6 mg/L for healthy neonates (21,27,28,59,60,62,68,72,89,90 ). Although the diagnostic usefulness is superior in neonates than in adults, application of CRP for diagnostic purposes is best left until 24 h after birth.…”
Section: Biomarker Detectionmentioning
confidence: 99%
“…Infection, sepsis: Clinical signs and symptoms of infection were divided into six categories according to Dollner et al [19]: (1) pallor and icterus; (2) lethargy, apnea, bradycardia, irritability and seizures; (3) tachypnea and dyspnea; (4) hypotension, tachycardia and compromised microcirculation; (5) vomiting and abdominal dystension; (6) fever and temperature instability.…”
Section: Classification Criteriamentioning
confidence: 99%
“…Infants in the suspected infection group had a sterile blood culture in the presence of clinical symptoms of infection (for example, apnea, temperature instability, feeding intolerance). 13 Controls were infants without clinical signs of infection.…”
Section: Patientsmentioning
confidence: 99%